Effectiveness of preoxygenation during endotracheal intubation in a head-elevated position : a systematic review and meta-analysis of randomized controlled trials - Samuel Ern Hung, Tsan; Navian Lee, Viknaswaran; Jiaying, Lau; Chao, Chia Cheong; Chew, Yin Wang (Polish Society of Anaesthesiology and Intensive Therapy, 2022)
Preoxygenation during endotracheal intubation is important to ensure the safety of the procedure. This systematic review and meta-analysis aimed to evaluate the efficacy of preoxygenation in the head-elevated position as compared to the supine position. The Medline, PubMed, Scopus, Embase, and CENTRAL databases were searched systematically from inception of the study until 29 June 2021. Only randomized controlled trials (RCTs) were included. The Cochrane Risk of Bias Assessment Tool and GRADE assessment of certainty of evidence were used. Seven RCTs (n = 508) were analysed, of which 6 were included in the meta-analysis (n = 227). Six studies were carried out in the operating theatre (OT), while one was performed in the critical care (ICU) setting. Compared to the supine position, the head-elevated position significantly increased the duration of the safe apnoea period (mean difference 61.99 s; 95% confidence interval 42.93–81.05 s; P < 0.00001; I 2 = 30%; certainty of evidence = high). This improvement was seen in both the obese and non-obese population (I 2 = 0%). No differences were seen between both groups with regard to recovery time after apnoea, arterial oxygen tension after preoxygenation, and the incidence of adverse events. In the ICU setting, no difference was found between groups for the incidence of hypoxaemia and the lowest oxygen saturation between induction and after intubation. This meta-analysis demonstrated that the head-elevated position significantly improved the efficacy of preoxygenation during elective intubation in the OT. Clinicians should consider the head-elevated position as a starting intubating position for all patients undergoing anaesthesia in view of its many benefits and the lack of proven adverse consequences. Protocol Registration: This systematic review was registered prospectively in PROSPERO (CRD42019128962)